FACTORS AFFECTING IMPLEMENTATION OF MEDICAL RECORDS MANAGEMENT ON SERVICE DELIVERY AMONG HEALTH WORKERS AT MASAKA REGIONAL REFERRAL HOSPITAL, MASAKA DISTRICT A CROSS-SECTIONAL SURVEY. - Martha Nakazibwe; Orishaba Glorious (Student's Journal of Health Research, 2023)
Background: The purpose of the study was to determine factors affecting the implementation of records management on service delivery among health workers at MRRH, district. The specific objectives were to find out; a health competency towards medical records management on service delivery, a health perception towards medical records management on service delivery, and health facility-based factors affecting the implementation of medical records management on service delivery. Methodology: A descriptive cross-sectional survey design was adopted for the study with a simple random sampling technique to select the sample from the study population. A self-administered questionnaire written in English and closed-ended questions was used as a data collection tool. Data were analyzed using Microsoft Excel. Results: Findings related to health competency towards medical records management on service delivery revealed that all respondents had ever heard about medical records management, (44%) knew medical records management endeavors easy retrieval of information, (40%) had fair computer skills, (50%) last attended any workshop on medical records management from a period of 1-2 years, (54%), irregularly manage medical records during service delivery and (52%) noted that medical management time-consuming. Conclusion: The researcher concluded that; inadequate computer skills, limited exposure to medical records management workshops, inadequate monitoring and evaluation strong team, lack of enough time, the task was perceived to be hectic, minimal mutual aid among health workers, Scant health workers, inadequate knowledge about the existence of policies and procedures for records management, among health were the overall factors affecting the implementation of medical records management on service delivery. Recommendation: The researcher recommended that MRRH administration should set and implement strategies that will enlighten health workers to have CPD points gained used for performance appraisal and promotion whenever opportunities arise to influence the implementation of records management during service delivery.